The Role of Interactive Learning Media in Improving Students' Learning Motivation of Islamic Education - Trajaya, Trajaya; Wijaya, Tomy; Nugroho, Amnur M. Ariya; Pratama, Win Dityo Jaya; Febriani, Evi (CV. Tripe Konsultan, 2025)
This study aims to explore the role of interactive learning media in enhancing students’ motivation to learn in Islamic Religious Education (PAI) subjects. In today’s digital era, the use of interactive media has become an essential innovation in the field of education. These media provide a more engaging and enjoyable learning experience, actively involving students in the learning process. The research method used is qualitative descriptive with data collected through observation, interviews, and documentation. The results show that interactive learning media, such as educational videos, interactive quizzes, and digital applications, are effective in increasing students' interest and participation in PAI lessons. Students became more enthusiastic, actively asked questions, and demonstrated improved understanding of the subject matter. In addition, teachers felt supported in delivering materials more effectively and efficiently. The conclusion of this study is that interactive learning media play a significant role in improving students' learning motivation, especially in PAI subjects, which are often perceived as monotonous by some students. Therefore, the development and utilization of interactive media should continue to be enhanced to create more meaningful and enjoyable learning experiences.